Effective theory approach to new physics with flavour: general framework and a leptoquark example - Marzia Bordone; Oscar Catà; Thorsten Feldmann (Journal of High Energy Physics)
Abstract Extending the Standard Model with higher-dimensional operators in an effective field theory (EFT) approach provides a systematic framework to study new physics (NP) effects from a bottom-up perspective, as long as the NP scale is sufficiently large compared to the energies probed in the experimental observables. However, when taking into account the different quark and lepton flavours, the number of free parameters in- creases dramatically, which makes generic studies of the NP flavour structure infeasible. In this paper, we address this issue in view of the recently observed “flavour anomalies” in B-meson decays, which we take as a motivation to develop a general framework that allows us to systematically reduce the number of flavour parameters in the EFT. This framework can be easily used in global fits to flavour observables at Belle II and LHCb as well as in analyses of flavour-dependent collider signatures at the LHC. Our formalism represents an extension of the well-known minimal-flavour-violation approach, and uses Froggatt-Nielsen charges to define the flavour power-counting. As a relevant illustration of the formalism, we apply it to the flavour structures which could be induced by a U1 vector leptoquark, which represents one of the possible explanations for the recent hints of flavour non-universality in semileptonic B-decays. We study the phenomenological viability of this specific framework performing a fit to low-energy flavour observables.